Autobiographical Narrative as a Tool of Studying Traumatic Memory - Vasyliuk, Olha (East European Journal of Psycholinguistics, 2014)
The paper presents the results of the theoretical and empirical study of the possibilities of using autobiographical narrative for diagnosing the traumatic memory of the individual. The views of foreign  and  local  psychologists  on the nature of the  generation of narrative, it’s using  as  a powerful psychotherapeutic   tool. The features of representation experience   and   selectivity   of   consciousness regarding  to  its  preservation  have  been  described.   The  empirical  study  was  based  on  the  method  of autobiographical   narrative   with   the   topic: “Traumatic   event   in   my   life”  and   Mississippi   scale   for assessing     post-traumatic    stress   reactions.   Based    on    the   data   analysis   of   psycholinguistic autobiographical narrative was created three-level scale ratio, that typical only for texts with traumatic content. We described the characteristics of psycholinguistic indicators, which can serve as guidelines in the diagnostic study of the traumatic experience of the individual. According to the features of writing autobiographical narrative by diagnosed, done its division into four types:  ambivalent, neutral, negative and positive. Estimated level of posttraumatic stress disorder of patients and based on these data, done the   analysis  of  the  relationship  between    the  type  of  autobiographical    narrative   and  the  level  of posttraumatic stress disorder. Offered and proved the feasibility of using autobiographical narrative as a diagnostic tool in the study of traumatic memory of the individual.  ReferencesBarclay, C. (1996). Autobiographical remembering: Narrative constraints on objectifiedselves. Remembering our past: Studies in autobiographical memory, 94–125.Brewer, W. (1986). What is autobiographical memory? Autobiographical memory, 25–49.Brown, R., Kulik, J. (1977). Flashbulb memories. Cognition, 5(1), 73–99.Zasiekina, L. (2012). Naratyvnyi dosvid vis-à-vis zdorovju osobystosti [Narrativeexperience vis-a-vis the health of individual]. Psychological Prospects, 19, 101–110.Kalmykova, E. (1998). Narrativ v psihoterapii: rasskazy pacyentov o lichnoj istorii[Narrative in psychotherapy: stories from patients about personal history]. Psychological Journal,19 (5), 97–103.Sarbin, T. (1986). Narratology as a root metaphor in psychology. Narrative Psychology:The Storied Nature of Human Conduct, 14–68.Shulevska, O. (2003). Psychologichni osoblyvosti porodzennja naratyvu jak zasobusamorozvytku osobystosti [Psychological features of producing narrative as a means of personality’sself-development]. Kyiv.